Incidence and management of hepatocellular carcinoma among Māori and non‐Māori New Zealanders. (29th October 2013) - Chamberlain, Joshua; Sarfati, Diana; Cunningham, Ruth; Koea, Jonathan; Gurney, Jason; Blakely, Tony
Abstract Objective: To investigate time trends in hepatocellular carcinoma (HCC) incidence disparities, and ethnic differences in risk factors, comorbidity and treatment pathways among HCC patients. Methods: Cohorts of the NZ population (1981–2004) were created and probabilistically linked to cancer registry records to investigate trends in incidence by ethnicity over time. Hospital notes of 97 Māori and 92 non‐Māori HCC patients diagnosed between 01/01/2006 and 31/12/2008 in NZ's North Island were reviewed. Results: Liver cancer incidence was higher among Māori for all time periods. Compared with non‐Māori, Māori males had nearly five times the rate of liver cancer (pooled RR=4.79, 95% CI 4.14–5.54), and Māori females three times the rate (pooled RR= 3.02, 95% CI 2.33–3.92). There were no significant differences in tumour characteristics or treatment of Māori and non‐Māori patients with HCC. Māori more commonly had hypertension (51% versus 25%) while more non‐Māori had cirrhosis recorded (62% versus 41%). The prevalence of hepatitis B among Māori patients (56%; 95% CI 45%‐67%) was more than double that of non‐Māori (27%; 95% CI 19%‐36%). The hazard ratio for cancer‐specific death for Māori compared with non‐Māori was 1.36 (95% CI 0.96–1.92). Conclusions and implications: HCC remains an important health problem particularly for Māori men. Efforts to improve coverage of screening for hepatitis B and surveillance of those with chronic hepatitis should be a priority to address the large inequalities found in liver cancer epidemiology.